Non-financial Disclosures as Contemporary Corporate Reporting – Definition, Sources and Proposed Research Directions - Bek-Gaik, Bogusława; Krasodomska, Joanna (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2018)
There is ever more debate surrounding the development of corporate reporting, in particular as regards non-financial disclosures. Three factors are responsible for that debate: rising criticism of traditional financial statements, growing stakeholder interest in all company resources and overall performance, as well as an evolution of the approach to corporate value creation. Additional forms of non-financial reporting, which are more and more common among companies, and integrated reporting in particular, prompt the need to determine the direction for corporate reporting and the role non-financial information is to play in its transformation. This paper presents a definition of non-financial disclosures, as well as their main sources, such as corporate social responsibility reporting, management commentary and integrated reporting. It indicates useful directions research in the area of non-financial reporting could take. The paper is based on a literature review, and also includes the results of the authors’ earlier studies, as well as observations on economic practices in the area of non-financial reporting.